A Comparison of the Effect of Reinforcement, Cost and Mixed Token Programs on the Attending Behaviour and Arithmetic Performance of "Learning Disabled" Children - Hundert, Phillip Joel (My University, 1973)
Eight children in a classroom for "learning disabled" children were used as subjects in an experiment designed to compare the relative effectiveness of a reinforcement token program, a response cost token program and a mixed token program. The effects of the three token programs were assessed by a within-subject comparison divided into three phases: i) baseline; ii) training; iii) withdrawal of tokens. The eight subjects were separated into a control group of two subjects who received only the mixed procedure throughout the training phase and an experimental composed of six subjects who received a counterbalanced sequence of all three of the conditioning procedures. It was found that, although the token programs as a whole increased the attending behaviour and academic performance of the subjects, there was no difference in effectiveness between the three conditioning procedures. Explanations for the findings were explored by examining the assumptions concerning possible mechanisms underlying reinforcement and punishment.
Keywords: Psychology; Psychology